2014
DOI: 10.1152/ajpendo.00523.2013
|View full text |Cite
|
Sign up to set email alerts
|

Connexin 36 mediates blood cell flow in mouse pancreatic islets

Abstract: The insulin-secreting β-cells are contained within islets of Langerhans, which are highly vascularized. Blood cell flow rates through islets are glucose-dependent, even though there are no changes in blood cell flow within in the surrounding exocrine pancreas. This suggests a specific mechanism of glucose-regulated blood flow in the islet. Pancreatic islets respond to elevated glucose with synchronous pulses of electrical activity and insulin secretion across all β-cells in the islet. Connexin 36 (Cx36) gap ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
(69 reference statements)
1
8
0
Order By: Relevance
“…The vascular dilation was similar to that elicited by high glucose concentrations in pancreas slices (Figure 5). We also quantified blood flow by counting red blood cells in the vascular lumen and found that blood flow increased in blood vessels (Figure 6H, Movies S4–S6), similarly to what has been reported for islets in the pancreas (Nyman et al, 2010; Short et al, 2014). These results indicate that raising glycemia increases islet blood flow through local dilation of capillaries in the islet microcirculation.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The vascular dilation was similar to that elicited by high glucose concentrations in pancreas slices (Figure 5). We also quantified blood flow by counting red blood cells in the vascular lumen and found that blood flow increased in blood vessels (Figure 6H, Movies S4–S6), similarly to what has been reported for islets in the pancreas (Nyman et al, 2010; Short et al, 2014). These results indicate that raising glycemia increases islet blood flow through local dilation of capillaries in the islet microcirculation.…”
Section: Resultssupporting
confidence: 78%
“…In pancreatic islets there is a positive correlation between endocrine cell activity and blood flow (Hellerstrom et al, 1960; Jansson et al, 2016). Hyperglycemia and its associated beta cell activation increase islet capillary blood pressure (Carlsson et al, 1997), dilate islet arterioles (Lai et al, 2007a), accelerate blood flow and increase blood volume (Nyman et al, 2010; Short et al, 2014). We hypothesized that activating beta cells with high glucose concentrations decreases islet pericyte activity, which relaxes pericytes and dilates capillaries.…”
Section: Resultsmentioning
confidence: 99%
“…However heterotypic channels (composed of connexons of two different connexin species) could potentially form between exocrine tissue or vasculature and β‐cells [65,66]. For example, a recent study has found a correlation between Cx36 expression and changes in glucose stimulated islet blood cell flow rates [67]. This suggests a connection between β‐cell electrical coupling and vascular regulation of blood flow; however the mechanism behind this regulation is still unclear.…”
Section: Connexin36 Regulation Of Insulin Secretionmentioning
confidence: 99%
“…27,30 Studies in Cx36 knockout animals have indicated that these gap junctions in b-cells not only regulate insulin secretion but also regulate intra-islet blood flow. 31 High fat fed mice, which show insulin resistance, obesity and pre-diabetes have a significant reduction in islet Cx36 protein and around 30% less b-cell to b-cell coupling. 32 These data suggest that Cx36 gap junctions are affected and may contribute to islet b-cell dysfunction during the progression from impaired glucose tolerance to Type 2 diabetes.…”
Section: Gap Junctions In the Pancreasmentioning
confidence: 99%